DESIGNING ONLINE LEARNING-BASED SYLLABUS AND MATERIALS FOR TOURISM DEPARTMENT STUDENTS IN BATAM INTERNATIONAL UNIVERSITY - Leil Badrah Zaki; Jonathan Alexander (PROJECT (Professional Journal of English Education), 2022)
Tourism industry nowadays requires tourism executives to master English as a universal language. Providing English materials for tourism can be conducted in universities through English for Specific Purpose (ESP) course. However, it is important to make sure that the syllabus and materials provided can fulfill students' learning needs. This research aims to design a syllabus and materials for tourism students at UIB based on their needs. However, due to COVID-19 pandemic, the materials are specifically designed for the students to learn through online. Plomp's R&D model was chosen as the research method. The subjects were forty tourism students on 1st semester, one UIB English lecturer, and four stakeholders. Based on the data, it is stated that the students need to focus more on enhancing their communication for the future. Speaking and listening are the skills that will be centred in the ESP course. Multi-syllabus is chosen as the type of syllabus that will be used which consists 14 meeting topics that were produced based on the need analysis. The materials used are PPT slides, YouTube link, audio files, lesson plans, and worksheet. The result shows that the students were satisfied with the implementation. The types of the syllabus and the materials were appropriate for the students. Keywords:  Tourism, English for Specific Purposes, Learning Needs, Materials, Communication